Optimizing small-scale geothermal power: insights from long-term testing and system modifications of a 3 MW geothermal condensing power plant in Kamojang, Indonesia - Agustina, Lina; Suyanto, Suyanto; Ismoyo, Budi (Institute of Advanced Engineering and Science, 2026)
This study presents the design, development, and performance evaluation of a 3 MW geothermal pilot power plant in Kamojang, Indonesia, developed by retrofitting a 2 MW backpressure turbine into a six-stage condensing turbine. With a 63.81% local content, the plant serves as one of Indonesia’s first demonstrations of small-scale condensing turbine technology. Multi-phase testing yielded a maximum net output of 2.2 MW, below the design target due to condenser vacuum inefficiencies, strainer pressure losses, and reduced turbine isentropic efficiency. Subsequent condenser and strainer modifications improved vacuum stability, reduced pressure drops, and enhanced specific steam consumption (SSC) and overall performance. Exergy analysis identified the condenser (16.1%) and turbine (9.5%) as the primary sources of exergy destruction, resulting in an overall exergy efficiency of 73.6%, higher than typical small-scale geothermal benchmarks. While operational performance improved significantly, sustaining long-term vacuum stability and optimizing turbine operation under variable steam conditions remain key challenges. Future work should focus on automated vacuum control, real-time monitoring, and advanced thermodynamic-electrical optimization to enhance system reliability. This study provides practical insights into turbine retrofitting, condenser stabilization, and integrated exergy evaluation, contributing to the advancement and localization of small-scale geothermal power technology in Indonesia.